A FORGOTTEN MODERNITY: Art Déco in Curitiba - Sutil, Marcelo Saldanha (Revista UFG, 2017)
Modernity was the watchword for people who lived through the 1920s and 30s. In itself, the word conjures up the meanings of things ranging from technological innovations to postwar years. It included speed, the automobile, the gramophone, radio, and even the housewife’s gas stove. The word modern described the latest fashion in vogue. Modernity, a concrete sign of emancipation and autonomy, was what had already been lived and the future in the pipeline. Even the past was modern one day. Modernity was architecture in the making. In a certain way, the adjective described everything that was then being built, and it was common to see the term used and defined as belonging to a cubic, futuristic, 1925-style Art Moderne, fascist, water tower style, Paris 25, Jazz Modern Style, La Mode 25 architecture (Almada and Conde, 2000) – and so on, in a series of names later brought together and defined simply as Art Déco, a term derived from the name of the 1925 Exposition Internationale des Arts Decoratifs et Industriels Modernes. (...)